Wind power blade composite material and preparation method thereof
By synthetic the combination of silicone -containing epoxy cross -linked agent and nano TiO2, the bipolar oxygen -organic silicon modified TiO2 is formed, which solves the problem of crispness and insufficient anti -ultraviolet performance of wind power blades. Anti -ultraviolet performance and humidity resistance aging performance.
Patent Information
- Application Number
- CN202411627656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
AI Technical Summary
The existing wind power blade composite materials have problems such as high brittleness, short application period, poor permeability and high curing temperature, which seriously affects the scope of application and service life of epoxy resin composite materials, and at the same time, they lack ultraviolet resistance.
By synthetic oxygenocurrency -containing oxyxane, a chemical bonding of hydroxyl groups on the surface of the nano -nano TiO2 is used to produce a chemical bond to form a bipolar oxygenic silicon. Prevention, improve the mechanical properties of composite materials and anti -ultraviolet performance.
It improves the toughness, anti -ultraviolet performance and humidity and heat aging performance of composite materials, extend the service life of the material, and enhance its stability in the high temperature and humidity environment.
Smart Images

Figure BDA0005135140310000031 
Figure BDA0005135140310000102 
Figure BDA0005135140310000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wind turbine blades, and in particular to a composite material for wind turbine blades and a preparation method thereof. Background Art
[0002] Wind power generation is an important clean energy source, and its development and utilization are receiving more and more attention from countries around the world. As a key component of a wind turbine, wind turbine blades play the role of capturing wind power and passing it on to the generator set. They are usually prepared using a vacuum infusion molding process, which is a process method in which the gas in the fiber reinforcement is removed under a vacuum state, the fiber and its fabric are impregnated through the flow and penetration of the resin, and a resin fiber composite material is formed after heating and curing. With the continuous development of wind power technology, the size of wind turbine blades is also increasing. Large blades can capture more wind energy and improve the power generation efficiency of wind turbines. However, the increase in blade length also puts higher requirements on materials. At the same time, wind turbine blades are outdoors all year round, exposed to ultraviolet radiation and in harsh environments, so higher requirements are placed on the mechanical properties, weather resistance and UV resistance of composite materials.
[0003] In the prior art, epoxy resin and glass fiber or carbon fiber are mostly used to prepare wind turbine blades. Since epoxy resin accounts for the largest proportion of the entire composite material, the performance of epoxy resin determines the quality and service life of the composite material for wind turbine blades; however, the existing epoxy resin-based fiber-reinforced composite materials have problems such as large material brittleness, short application period, poor permeability and high curing temperature, which seriously affect the application scope and service life of the epoxy resin composite material; Patent No. CN110437587B discloses a carbon fiber composite material resin for wind turbine blades and a preparation method thereof, comprising the following components: 70-80 parts of epoxy resin, 10-20 parts of toughening resin, 6-10 parts of nano rubber particles, 3-10 parts of powdered filler, 5-12 parts of carbon fiber and 24-40 parts of amine curing agent. The prepared composite material tree meets the special requirements of wind turbine blades above megawatt level for materials, and the preparation process is simple and the comprehensive performance is good, but the weather resistance and toughness of the composite material need to be further improved, and the anti-ultraviolet performance has not been effectively improved.
[0004] Carbon fiber has low density, high tensile strength and chemical resistance, but it has disadvantages such as high brittleness and poor toughness. Polyimide fiber has good toughness and ductility, which can make up for the shortcomings of carbon fiber itself. Nano-TiO 2 It has the function of shielding and absorbing ultraviolet rays, but its nano-sized particles have high surface energy and are prone to agglomeration in the polymer matrix, which seriously affects its anti-ultraviolet performance. The present invention aims to synthesize an epoxy crosslinking agent containing siloxane, and utilize the trimethoxysilane in its structure to hydrolyze and react with nano-TiO 2The hydroxyl groups on the surface produce chemical bonds, and the diepoxy groups are similarly compatible with bisphenol A epoxy resin. They can be used as a diluent to reduce viscosity, and can also be used as a toughening agent to provide heat and weather resistance and improve mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a wind turbine blade composite material and a preparation method thereof, which has good heat resistance, weather resistance and strong UV resistance.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a wind turbine blade composite material comprises the following steps:
[0008] Step (1), under nitrogen atmosphere, add bisphenol A epoxy resin and diepoxy silicone modified TiO 2 After stirring evenly, add methyltetrahydrophthalic anhydride and 2,6-di-tert-butyl-p-cresol, stir to react, cool to room temperature after the reaction is completed, vacuum degassing for 25-40 minutes, and naturally cool to room temperature to obtain cyclic organosilicon TiO2 modified epoxy resin.
[0009] Step (2), using a vacuum infusion process, laying the cut polyimide fibers and carbon fibers layer by layer in a dipping tank to form mixed fibers, pre-pressing for 20-40 minutes at a vacuum degree of 120-200 kPa, pouring the cyclic organosilicon TiO2 modified epoxy resin into the dipping tank from the glue inlet at room temperature, impregnating from the upper surface to the lower surface of the mixed fibers, the infusion time is 15-25 minutes, and then adding an amine curing agent, curing at 65-80°C for 5-10 hours, to obtain a wind turbine blade composite material.
[0010] Preferably, in step (1), bisphenol A epoxy resin, diepoxy silicone modified TiO 2 The ratio of methyltetrahydrophthalic anhydride and 2,6-di-tert-butyl-p-cresol is 100g:(5-25)g:(20-35)g:(0.5-1.2)g.
[0011] Preferably, in step (1), the reaction temperature is 90-105° C. and the reaction time is 2-5 h.
[0012] Preferably, the amine curing agent in step (2) is any one of diethylenetriamine, isophoronediamine or 4,4-diaminodiphenyl sulfone.
[0013] Preferably, in step (1), the diepoxy silicone modified TiO 2 The preparation method comprises the following steps:
[0014] Step (3), under nitrogen atmosphere, add 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid and toluene to a reaction flask equipped with a thermometer and a reflux condenser, stir evenly, add allyl glycidyl ether, react at 50-70°C for 1-2h, add allyl trimethoxysilane and tert-butyl hydroquinone, react at 80-100°C for 3-6h, cool to room temperature, and concentrate under reduced pressure to obtain an epoxy silicone modifier. The preparation reaction formula is as follows:
[0015]
[0016] Step (4), under nitrogen atmosphere, add nano-TiO 2 After being uniformly dispersed by ultrasonic, epoxy silicone modifier and dibutyltin dilaurate were added, stirred for reaction, and after the reaction was completed, centrifuged, washed alternately with toluene and ethanol, and dried in vacuum to obtain diepoxy silicone modified TiO 2 .
[0017] Preferably, in step (3), the ratio of 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid, allyl glycidyl ether, allyl trimethoxysilane, and tert-butylhydroquinone is 1 mol: (0.01-0.025) mol: (1.9-2.1) mol: (2.3-2.5) mol: (0.002-0.004) mol.
[0018] Preferably, in step (4), the nano-TiO 2 The ratio of epoxy silicone modifier to dibutyltin dilaurate is 100g:(20-30)g:(3-5)g.
[0019] Preferably, in step (4), the reaction temperature is 75-100° C. and the reaction time is 5-12 h.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) Bis-epoxy silicone modified TiO 2 It has a similar structure to epoxy resin, which improves the interfacial compatibility between the two and makes nano-TiO 2It can be evenly dispersed in the polymer matrix, which is beneficial to the transfer of stress loads. When subjected to external forces, it can consume some impact energy and improve the toughness of the composite material. The epoxy groups in its structure can easily bond with the oxygen in the epoxy resin to produce a strong hydrogen bond force, which to a certain extent hinders the expansion of microcracks and forms a "pinning" effect. The cyclic siloxane structure facilitates the slip and rearrangement between molecular chains, making the composite material have higher flexibility and elasticity. In addition, polyimide fibers can absorb energy through deformation, making up for the brittleness of carbon fibers. The mixing of the two fibers makes the load transfer in the composite material more diverse, produces a positively correlated synergistic effect, and significantly improves the mechanical properties of the composite material.
[0022] (2) Bis-epoxy silicone modified TiO 2 It can be evenly dispersed in the epoxy resin matrix. The mesopores on its surface can stably absorb ultraviolet light in the medium and long wave regions. The absorption and scattering of ultraviolet light constitute a shielding effect on ultraviolet light. When ultraviolet light reaches the nano-TiO 2 When the surface of nano-TiO2 is exposed, its valence band electrons absorb the energy of ultraviolet rays and are excited to jump from the valence band to the conduction band, thereby forming photogenerated electrons. The photogenerated electrons are captured by oxygen in the air to generate superoxide radicals, which can oxidize organic pollutants to generate carbon dioxide and water. Therefore, nano-TiO2 2 It has good absorption of ultraviolet light, weakens the damage of ultraviolet light and improves the anti-ultraviolet performance of the composite material.
[0023] (3) Bis-epoxy silicone modified TiO 2 The addition of TiO2 can increase the contact area with epoxy resin and mixed fibers, which is beneficial to the entanglement of epoxy resin and the formation of physical crosslinking. The epoxy groups in its structure are easy to bond with epoxy resin during curing, forming a tight molecular chain crosslinking structure. During the heating process of the composite material, nano-TiO 2 Gradually transferred to the surface of the material, forming a three-dimensional network structure protective layer, protecting the inner layer material from erosion by external heat, and greatly improving the resistance of the composite material to moisture and heat aging. The wind turbine blade composite material prepared in this application meets the special material requirements of wind turbine blades above megawatt level, and has a simple preparation process and a wide range of applications. DETAILED DESCRIPTION
[0024] The following examples are provided to further illustrate the present invention, but they are not to be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in the field according to the above content of the present invention still belong to the scope of protection of the present invention. Unless otherwise specified, the raw materials and reagents used in this application are all commercially available products, or can be prepared by known methods.
[0025] Polyimide fiber: linear density 55.5tex, density 1.49g / cm 3 , purchased from Jiangsu Aoshen New Materials Co., Ltd.
[0026] Carbon fiber: specification 12K, linear density 442tex, density 1.79g / cm 3 , purchased from Zhongfu Shenying Carbon Fiber Co., Ltd.
[0027] Bisphenol A epoxy resin: Model 6101, purchased from Jiangsu Sanmu Group.
[0028] 2,4,6,8-Tetramethylcyclotetrasiloxane: CAS number is 2370-88-9.
[0029] Allyl glycidyl ether: CAS number is 106-92-3.
[0030] Allyltrimethoxysilane: CAS number is 1476-23-9.
[0031] Example 1
[0032] (1) Under a nitrogen atmosphere, 45 mmol of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.9 mmol of chloroplatinic acid and 180 mL of toluene were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 90 mmol of allyl glycidyl ether was added and the mixture was reacted at 60° C. for 1.5 h. 100 mmol of allyl trimethoxysilane and 0.144 mmol of tert-butyl hydroquinone were added and the mixture was reacted at 90° C. for 5 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an epoxy silicone modifier.
[0033] (2) Under nitrogen atmosphere, add 20 g of nano-TiO 2 and 200 mL toluene, after ultrasonic dispersion, 4 g epoxy silicone modifier and 0.84 g dibutyltin dilaurate were added, reacted at 85 ° C for 8 h, centrifuged, washed alternately with toluene and ethanol, and vacuum dried to obtain diepoxy silicone modified TiO 2 .
[0034] (3) Under nitrogen atmosphere, 100 g of bisphenol A epoxy resin and 5 g of diepoxy silicone-modified TiO 2 After stirring evenly, 25 g of methyltetrahydrophthalic anhydride and 0.8 g of 2,6-di-tert-butyl-p-cresol were added, reacted at 100 °C for 4 h, cooled to room temperature, vacuum degassed for 30 min, and naturally cooled to room temperature to obtain cyclic organosilicon TiO 2 Modified epoxy resin.
[0035] (4) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 150 kPa for 30 min. The cyclic organosilicon TiO2-modified epoxy resin was poured into the dipping tank from the inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 20 min. Diethylenetriamine was then added and the mixture was cured at 75 °C for 8 h to obtain a composite material for wind turbine blades.
[0036] Example 2
[0037] (1) Under a nitrogen atmosphere, 220 mmol of 2,4,6,8-tetramethylcyclotetrasiloxane, 2.2 mmol of chloroplatinic acid and 660 mL of toluene were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 418 mmol of allyl glycidyl ether was added and the mixture was reacted at 70° C. for 1 h. 506 mmol of allyl trimethoxysilane and 0.44 mmol of tert-butyl hydroquinone were added and the mixture was reacted at 100° C. for 3 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an epoxy silicone modifier.
[0038] (2) Under nitrogen atmosphere, add 35 g of nano-TiO 2 and 280 mL toluene, after ultrasonic dispersion, 7.7 g epoxy silicone modifier and 1.05 g dibutyltin dilaurate were added, reacted at 100 ° C for 5 h, centrifuged, washed alternately with toluene and ethanol, and vacuum dried to obtain diepoxy silicone modified TiO 2 .
[0039] (3) Under nitrogen atmosphere, 100 g of bisphenol A epoxy resin and 10 g of diepoxy silicone-modified TiO 2 After stirring evenly, 20 g of methyltetrahydrophthalic anhydride and 0.5 g of 2,6-di-tert-butyl-p-cresol were added, reacted at 105 °C for 2 h, cooled to room temperature, vacuum degassed for 40 min, and naturally cooled to room temperature to obtain cyclic organosilicon TiO 2 Modified epoxy resin.
[0040] (4) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 200 kPa for 20 min. The cyclic organosilicon TiO2-modified epoxy resin was poured into the dipping tank from the inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 15 min. Then, isophorone diamine was added and the mixture was cured at 80 °C for 5 h to obtain a wind turbine blade composite material.
[0041] Example 3
[0042] (1) Under a nitrogen atmosphere, 30 mmol of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.75 mmol of chloroplatinic acid and 150 mL of toluene were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 63 mmol of allyl glycidyl ether was added and the mixture was reacted at 50° C. for 2 h. 75 mmol of allyl trimethoxysilane and 0.12 mmol of tert-butyl hydroquinone were added and the mixture was reacted at 80° C. for 6 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an epoxy silicone modifier.
[0043] (2) Under nitrogen atmosphere, add 15 g of nano-TiO 2 and 180 mL toluene, after ultrasonic dispersion, 3.75 g epoxy silicone modifier and 0.75 g dibutyltin dilaurate were added, reacted at 75 ° C for 12 h, centrifuged, washed alternately with toluene and ethanol, and vacuum dried to obtain diepoxy silicone modified TiO 2 .
[0044] (3) Under nitrogen atmosphere, 100 g of bisphenol A epoxy resin and 15 g of diepoxy silicone-modified TiO 2 After stirring evenly, 35 g of methyltetrahydrophthalic anhydride and 1.2 g of 2,6-di-tert-butyl-p-cresol were added, reacted at 90 °C for 5 h, cooled to room temperature, vacuum degassed for 40 min, and naturally cooled to room temperature to obtain cyclic organosilicon TiO 2 Modified epoxy resin.
[0045] (4) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 120 kPa for 40 min. The cyclic organosilicon TiO2-modified epoxy resin was poured into the dipping tank from the inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 25 min. Then, 4,4-diaminodiphenyl sulfone was added and the mixture was cured at 65 °C for 10 h to obtain a wind turbine blade composite material.
[0046] Example 4
[0047] (1) Under nitrogen atmosphere, 12 mmol of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.28 mmol of chloroplatinic acid and 42 mL of toluene were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 23.4 mmol of allyl glycidyl ether was added and the mixture was reacted at 65° C. for 2 h. 150.8 mmol of allyl trimethoxysilane and 0.042 mmol of tert-butyl hydroquinone were added and the mixture was reacted at 95° C. for 5 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an epoxy silicone modifier.
[0048] (2) Under nitrogen atmosphere, add 18 g of nano-TiO 2 and 190 mL toluene, after ultrasonic dispersion, 4.86 g epoxy silicone modifier and 0.81 g dibutyltin dilaurate were added, reacted at 85 °C for 9 h, centrifuged, washed alternately with toluene and ethanol, and vacuum dried to obtain diepoxy silicone modified TiO 2 .
[0049] (3) Under nitrogen atmosphere, 100 g of bisphenol A epoxy resin and 20 g of diepoxy silicone-modified TiO 2 After stirring evenly, 32 g of methyltetrahydrophthalic anhydride and 1 g of 2,6-di-tert-butyl-p-cresol were added, reacted at 95 °C for 4 h, cooled to room temperature, vacuum degassed for 35 min, and naturally cooled to room temperature to obtain cyclic organosilicon TiO 2 Modified epoxy resin.
[0050] (4) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 160 kPa for 25 min. The cyclic organosilicon TiO2-modified epoxy resin was poured into the dipping tank from the inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 20 min. Diethylenetriamine was then added and the mixture was cured at 70 °C for 9 h to obtain a composite material for wind turbine blades.
[0051] Example 5
[0052] (1) Under a nitrogen atmosphere, 50 mmol of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.9 mmol of chloroplatinic acid and 185 mL of toluene were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 98 mmol of allyl glycidyl ether was added and the mixture was reacted at 55° C. for 2 h. 121 mmol of allyl trimethoxysilane and 0.14 mmol of tert-butyl hydroquinone were added and the mixture was reacted at 85° C. for 5 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an epoxy silicone modifier.
[0053] (2) Under nitrogen atmosphere, add 5 g of nano-TiO 2 and 55 mL toluene, after ultrasonic dispersion, 1.5 g epoxy silicone modifier and 0.21 g dibutyltin dilaurate were added, reacted at 85 °C for 12 h, centrifuged, washed alternately with toluene and ethanol, and vacuum dried to obtain diepoxy silicone modified TiO 2 .
[0054] (3) Under nitrogen atmosphere, 100 g of bisphenol A epoxy resin and 25 g of diepoxy silicone-modified TiO2 After stirring evenly, 28 g of methyltetrahydrophthalic anhydride and 0.9 g of 2,6-di-tert-butyl-p-cresol were added, reacted at 100 °C for 3 h, cooled to room temperature, vacuum degassed for 30 min, and naturally cooled to room temperature to obtain cyclic organosilicon TiO 2 Modified epoxy resin.
[0055] (4) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 160 kPa for 35 min. The cyclic organosilicon TiO2-modified epoxy resin was poured into the dipping tank from the inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 25 min. Then, isophorone diamine was added and cured at 75 °C for 6 h to obtain a wind turbine blade composite material.
[0056] Comparative Example 1
[0057] (1) In a nitrogen atmosphere, 45 mmol of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.9 mmol of chloroplatinic acid and 180 mL of toluene were added to a reaction flask equipped with a thermometer and a reflux condenser. After stirring evenly, 180 mmol of allyl glycidyl ether was added, and the mixture was reacted at 90° C. for 5 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an epoxy silicone modifier (structural formula: ).
[0058] (3) Under a nitrogen atmosphere, 100 g of bisphenol A epoxy resin and 5 g of epoxy silicone modifier were added to a reaction flask. After stirring evenly, 25 g of methyltetrahydrophthalic anhydride and 0.8 g of 2,6-di-tert-butyl-p-cresol were added. The mixture was reacted at 100 °C for 4 h, cooled to room temperature, vacuum-degassed for 30 min, and naturally cooled to room temperature to obtain silicone-modified epoxy resin.
[0059] (3) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 150 kPa for 30 min. Silicone-modified epoxy resin was poured into the dipping tank from the inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 20 min. Diethylenetriamine was then added and the mixture was cured at 75 °C for 8 h to obtain a composite material for wind turbine blades.
[0060] Comparative Example 2
[0061] (1) Under nitrogen atmosphere, add 20 g of nano-TiO 2 and 200 mL of toluene, after ultrasonic dispersion, add 4 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS No. 2530-83-8, structural formula ) and 0.84 g of dibutyltin dilaurate were reacted at 85 ° C for 8 h, centrifuged, washed alternately with toluene and ethanol, and vacuum dried to obtain epoxy-modified TiO 2 .
[0062] (2) Under nitrogen atmosphere, add 100 g of bisphenol A epoxy resin and 5 g of epoxy-modified TiO 2 After stirring evenly, 25 g of methyltetrahydrophthalic anhydride and 0.8 g of 2,6-di-tert-butyl-p-cresol were added, reacted at 100 °C for 4 h, cooled to room temperature, vacuum degassed for 30 min, and naturally cooled to room temperature to obtain TiO 2 Modified epoxy resin.
[0063] (3) The cut polyimide fibers and carbon fibers were laid layer by layer in a dipping tank using a vacuum infusion process to form mixed fibers. The fibers were pre-pressed for 30 min at a vacuum degree of 150 kPa and TiO 2 The modified epoxy resin was poured into the dipping tank from the glue inlet, and impregnated from the upper surface to the lower surface of the mixed fiber for 20 minutes. Then diethylenetriamine was added and cured at 75°C for 8 hours to obtain a wind turbine blade composite material.
[0064] Comparative Example 3
[0065] The vacuum infusion process was used to lay the cut carbon fibers layer by layer in the dipping tank to form mixed fibers. The fibers were pre-pressed at a vacuum degree of 150 kPa for 30 minutes. Bisphenol A epoxy resin was poured into the dipping tank from the glue inlet at room temperature and impregnated from the upper surface to the lower surface of the mixed fibers. The infusion time was 20 minutes. Diethylenetriamine was then added and cured at 75°C for 8 hours to obtain a wind turbine blade composite material.
[0066] Tensile properties: Tested in accordance with GB / T 2568-1995 standard.
[0067] Bending performance: Tested in accordance with GB / T 9341-2000 standard.
[0068] Glass transition temperature: Tested in accordance with GB / T 19466.2-2004 standard.
[0069] Table 1 Mechanical properties test
[0070]
[0071]
[0072] From the test results in the above table, it can be seen that with the modification of TiO 2With the increase of content, the mechanical properties of the composite material gradually increase, and it has good toughness, mechanical properties and heat resistance. This is because on the one hand, the diepoxy silicone modified TiO 2 It has a similar structure to epoxy resin, which improves the interfacial compatibility between the two and makes nano-TiO 2 It can be evenly dispersed in the polymer matrix, which is beneficial to the transmission of stress loads. When subjected to external forces, it can consume some impact energy and improve the toughness of the composite material. At the same time, the diepoxy silicone modified TiO 2 The epoxy groups can easily form bonds with oxygen in epoxy resin, generating strong hydrogen bonding forces, which hinder the expansion of microcracks to a certain extent and form a "pinning" effect; on the other hand, the cyclic siloxane groups help the slip and rearrangement between molecular chains, making the composite material have higher flexibility and elasticity. In addition, polyimide fibers can absorb energy through deformation, making up for the brittleness of carbon fibers. The mixing of the two fibers makes the load transfer in the composite material more diverse, producing a positively correlated synergistic effect. 2 Comparative Example 2 does not contain cyclic siloxane groups and does not play a synergistic role; Comparative Example 3 adds pure epoxy resin and carbon fiber, does not contain polyimide fiber toughening, and cannot achieve the good toughness and mechanical properties of the composite material of the present application.
[0073] Anti-ultraviolet performance test: The prepared composite material was made into rectangular specimens, placed in an ultraviolet accelerated aging box, irradiated with a 200W mercury light source for 30 days, and the tensile strength test was carried out according to GB / T 2568-1995 standard.
[0074] Table 2 Anti-ultraviolet performance test
[0075] Tensile strength(MPa) Example 1 74.7 Example 2 81.0 Example 3 90.2 Example 4 98.9 Example 5 103.1 Comparative Example 1 59.2 Comparative Example 2 66.5 Comparative Example 3 48.7
[0076] From the test results in the above table, it can be seen that with the modification of TiO 2 With the increase of TiO content, the anti-ultraviolet performance of the composite material gradually increases. This is because the modified TiO 2 It can be evenly dispersed in the epoxy resin matrix. The mesopores on its surface can stably absorb ultraviolet light in the medium and long wave regions. The absorption and scattering of ultraviolet light constitute a shielding effect on ultraviolet light. When ultraviolet light reaches the nano-TiO 2 When the surface of nano-TiO2 is exposed, its valence band electrons absorb the energy of ultraviolet rays and are excited to jump from the valence band to the conduction band, thereby forming photogenerated electrons. The photogenerated electrons are captured by oxygen in the air to generate superoxide radicals, which can oxidize organic pollutants to generate carbon dioxide and water. Therefore, nano-TiO2 2 It has good absorption of ultraviolet light, reduces the damage of ultraviolet light to the composite material, and improves the anti-ultraviolet performance.2 , it does not have UV resistance and its tensile strength decreases significantly.
[0077] Resistance to moisture and heat aging: The prepared composite material was made into rectangular specimens and placed in an aging test box at a temperature of 85°C and a humidity of 95%. It was subjected to continuous moisture and heat aging for 30 days, and the bending strength test was carried out according to GB / T 9341-2000 standard.
[0078] Table 3 Test of moisture and heat aging resistance
[0079]
[0080]
[0081] Bis-epoxy silicone modified TiO 2 The addition of TiO2 can increase the contact area with epoxy resin and mixed fibers, which is beneficial to the entanglement of epoxy resin and the formation of physical crosslinking. The epoxy groups in its structure are easy to bond with epoxy resin during curing, forming a tight molecular chain crosslinking structure. During the heating process of the composite material, nano-TiO 2 It gradually transfers to the surface of the material to form a three-dimensional network structure protective layer, protecting the inner layer material from erosion by external heat, greatly improving the moisture-heat aging resistance of the composite material.
[0082] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the various possible combinations of the present invention will not be described separately.
Claims
1. A method for preparing a composite material for a wind turbine blade, characterized in that: The preparation method comprises the following steps: Step (1), under a nitrogen atmosphere, add bisphenol A epoxy resin and diepoxy silicone modified TiO2 into a reaction flask, stir evenly, add methyltetrahydrophthalic anhydride and 2,6-di-tert-butyl-p-cresol, stir to react, cool to room temperature after the reaction is completed, vacuum degassing for 25-40 minutes, and naturally cool to room temperature to obtain a cyclic silicone TiO2 modified epoxy resin; Step (2), using a vacuum infusion process, laying the cut polyimide fibers and carbon fibers layer by layer in a dipping tank to form mixed fibers, pre-pressing for 20-40 minutes at a vacuum degree of 120-200 kPa, pouring the cyclic organosilicon TiO2 modified epoxy resin into the dipping tank from the glue inlet at room temperature, impregnating from the upper surface to the lower surface of the mixed fibers, the infusion time is 15-25 minutes, and then adding an amine curing agent, curing at 65-80°C for 5-10 hours, to obtain a wind turbine blade composite material.
2. The method for preparing a composite material for wind turbine blades according to claim 1, characterized in that: In the step (1), the ratio of bisphenol A epoxy resin, diepoxy silicone modified TiO2, methyltetrahydrophthalic anhydride and 2,6-di-tert-butyl-p-cresol is 100g:(5-25)g:(20-35)g:(0.5-1.2)g.
3. The method for preparing a composite material for wind turbine blades according to claim 1, characterized in that: In the step (1), the reaction temperature is 90-105° C. and the reaction time is 2-5 h.
4. The method for preparing a composite material for wind turbine blades according to claim 1, characterized in that: In the step (2), the amine curing agent is any one of diethylenetriamine, isophoronediamine or 4,4-diaminodiphenyl sulfone.
5. The method for preparing a composite material for wind turbine blades according to claim 1, characterized in that: The method for preparing diepoxy silicone-modified TiO2 in step (1) comprises the following steps: Step (3), under a nitrogen atmosphere, add 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid and toluene to a reaction flask equipped with a thermometer and a reflux condenser, stir evenly, add allyl glycidyl ether, react at 50-70° C. for 1-2 h, add allyl trimethoxysilane and tert-butylhydroquinone, react at 80-100° C. for 3-6 h, cool to room temperature, and concentrate under reduced pressure to obtain an epoxy organosilicon modifier; Step (4), under a nitrogen atmosphere, add nano-TiO2 and toluene to a reaction flask equipped with a thermometer and a reflux condenser, and after ultrasonic dispersion, add an epoxy silicone modifier and dibutyltin dilaurate, stir to react, and after the reaction is completed, centrifuge, wash alternately with toluene and ethanol, and vacuum dry to obtain diepoxy silicone modified TiO2.
6. The method for preparing a composite material for wind turbine blades according to claim 5, characterized in that: In the step (3), the ratio of 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid, allyl glycidyl ether, allyl trimethoxysilane and tert-butylhydroquinone is 1 mol: (0.01-0.025) mol: (1.9-2.1) mol: (2.3-2.5) mol: (0.002-0.004) mol.
7. The method for preparing a composite material for wind turbine blades according to claim 5, characterized in that: In the step (4), the ratio of nano-TiO2, epoxy silicone modifier and dibutyltin dilaurate is 100g:(20-30)g:(3-5)g.
8. The method for preparing a composite material for wind turbine blades according to claim 5, characterized in that: In the step (4), the reaction temperature is 75-100° C. and the reaction time is 5-12 h.
9. A composite material for wind turbine blades, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A carbon fiber composite resin for wind turbine blades and its preparation method
CN110437587B
Cited By
Far-stable near-solid type nano sand consolidation agent and preparation method thereof
CN120888290A